PENANGANAN INSTRUKSIONAL BAGI ANAK LAMBAT BELAJAR (SLOW LEARNER) - admin admin; Nur Khabibah (Universitas Muhammadiyah Gresik, 2013)
Each child has a unique and different character. If in one class there are twenty-eight students, then there are twenty-eight different treatments that must be given by an educator. However, such treatment should not cause any jealousy among learners. All children have special needs, but when viewed in general, children with special needs is a child who really needs special handling because of its behavior or deviate from the kids in general. Slow learners child have unique characteristics with a variety of learning problems faced in school. To optimize their potential, it needs a special program designed to suit the educational needs of each individual.